ERASMUS, Hendrik Schalk Inventory of documents - ERASMUS, Hendrik Schalk (ARCA, 2018)
Private papers of H.S. Erasmus, National Party MP Hoopstad [1943-1948], Boshof-Hoopstad [1948-1953], Odendaalsrus [1953-1958].
COVERAGE 1940-1963; 4 Files; 0,23 Metre
Keywords: ERASMUS, Hendrik Schalk; Inventories; Politicians; National Party